The Use Of Communicative Language Teaching In Teaching Narrative Text Writing At Grade XII Of SMA Negeri 1 Siantar - Bella Sianturi; Selviana Napitupulu (Journal Innovative Practices in Education (JIPE), 2026)
This study aimed to investigate the effectiveness of Communicative Language Teaching (CLT) in improving students’ ability to write narrative texts at Grade XII of SMA Negeri 1 Siantar. The research employed a Classroom Action Research (CAR) design consisting of two cycles, each involving planning, acting, observing, and reflecting stages. The participants were 32 students of Class XII-Science 2 in the academic year 2024/2025. Data were collected through writing tests, observation sheets, and field notes. Quantitative data were obtained from pre-test and post-tests to measure students’ writing performance, while qualitative data were used to examine students’ participation, motivation, and classroom interaction during the implementation of CLT. The findings indicated a significant improvement in students’ narrative writing skills, particularly in content development, organization, vocabulary use, grammatical accuracy, and mechanics. In addition, students showed higher engagement, confidence, and collaboration during communicative writing activities such as group discussions, storytelling, and peer feedback. The results suggest that Communicative Language Teaching is an effective and meaningful approach for enhancing students’ narrative writing ability and creating a more interactive learning environment. Therefore, it is recommended that English teachers apply CLT-based strategies in writing instruction to improve students’ communicative competence and writing proficiency.